Sanksi Pidana Penyimpangan Seksual Sesama Jenis Terhadap Anak Sebagai Korban - Kadek Pageh Arimbawa; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2024)
Same-sex sexual deviance prohibited by Article 292 of the Criminal Code is only allowed if the victim is an adult and the perpetrator is a child. In relation to the issue of LGBT sexual deviance, the author views this as an odd norm. With this background, the author can formulate two problems: what are the criminal sanctions against same-sex deviant acts committed against children as victims? and how are legal arrangements for such acts made? This research method is normative legal research. Both a statutory approach and a conceptual analysis approach are used in this research. This tactic is also called the legal approach. The study findings revealed that Indonesia passed a law regulating same-sex crimes with minors as victims in 1946. Law of the Republic of Indonesia No. 2014 No. 35 on Modification. Law 23 of 2002 mostly regulates child protection. Criminal sanctions for same-sex sexual deviance refer to some of the severe penalties that can be threatened or imposed on people who commit or assist in committing crimes listed in Article 292 of Law No. Criminal law.